Protein-based polymer liquid embolics for cerebral aneurysms. (1st October 2022) - Jensen, Mark M.; Hatlevik, Øyvind; Steinhauff, D. Douglas; Griswold, Ethan D.; Wei, Xiaomei; Isaacson, Kyle J.; Barber, Zachary B.; Huo, Eugene; Taussky, Philipp; Jedrzkiewicz, Jolanta; Cappello, Joseph; Cheney, Darwin; et al.
Abstract: Cerebral aneurysms (CA), an abnormal bulge in the arteries that supply blood to the brain, are prone to rupture and can cause hemorrhagic stroke. Physicians can treat CA by blocking blood flow to the aneurysmal sac via clipping of the aneurysm neck via open procedure, or endovascular occlusion of the aneurysm with embolic materials to promote thrombus formation to prevent further inflow of blood into the aneurysm. Endovascular treatment options for CA still have significant limitations in terms of safety, usability in coagulopathic patients, and risks of device migration. Bioactive embolic therapies, consisting of non-toxic bioresorbable materials that encourage the growth of neointima across the aneurysm neck, are needed to improve the healing of CA. In this work, the bioinspired silk-elastinlike protein-based polymer (SELP 815K), was used to embolize aneurysms in a rabbit elastase model. SELP 815K effectively embolized the model aneurysms in vivo, achieving >90% occlusion, using commercial microcatheters. No device-associated adverse effects were observed in any of the animals, and SELP 815K showed no cytotoxicity. SELP embolization did not show any deleterious effects to local tissues, and features consistent with reendothelialization of the aneurysm neck were noted in histological examination one-month post-embolization. SELP 815K shows promise as an embolic treatment for unruptured CA. Statement of significance: Unruptured cerebral aneurysms are present in approximately 3% of the population, with a fatality rate of up to 65% upon rupture. In this work a silk-elastinlike protein polymer (SELP) is explored as a liquid embolic for occlusion of cerebral aneurysms. This embolic exists as a liquid at room temperature before rapidly forming a gel at physiological temperature. This shape filling property was used to successfully occlude cerebral aneurysms in rabbits, with stable occlusion persisting for over thirty days. SELP occlusions show evidence for reendothelialization of the aneurysm sac and provide an opportunity for delivery of bioactive agents to further improve treatments. Graphical abstract: Graphical Abstract. SELP liquid embolic mode of action. shows a cerebral aneurysm, the intended treatment target for SELP liquid embolic. Two angiogram still frames of the elastase- induced rabbit animal model pre- and post-embolization with SELP 815K. The red box highlights the treated aneurysm, and the small black circle is a 6.1 mm diameter calibration. Illustrations show the insertion of the balloon and microcatheter, the inflation of the balloon, followed by the injection of the SELP liquid embolic, the physical transformation of the SELP liquid embolic from a solution of polymer strands to a physical gel, followed by the removal of the microcatheter and the balloon. Image, graphical abstract